EXAMINATION OF LENS EXPOSURE DOSES OF CARDIOLOGISTS, NEUROSURGEONS AND RADIOLOGISTS IN INTERVENTIONAL RADIOLOGY. Issue 20 (1st November 2022) - Osawa, Mitsuharu; Tawada, Yuka; Kaneda, Naoki; Fujita, Naotoshi; Koyama, Shuji
Abstract: The International Commission on Radiological Protection (ICRP) 118th recommendation significantly reduced the threshold dose for cataract development from 8 to 0.5 Gy. Equivalent dose limits for the crystalline lenses of radiation workers are being reviewed for individual countries. Interventional radiology (IR) procedures are less invasive than surgery and have become widespread; however, there are concerns about exposure not only to patients but also to staff, including operators. Therefore, in this study, we used a human phantom to measure the near-lens dose of the operators (cardiologists, neurosurgeons and radiologists) and estimated the operator's lens dose for every major procedure in each clinical department; this was found to vary. Owing to the different imaging and fluoroscopy conditions of each department, and the varying ratio of fluoroscopy to radiography, it is necessary to measure the lens dose for each condition, as in this study. In addition, this study explains the differences between the protective effect of various safety equipment and the appropriate use of protective plates; it can contribute to the reduction of lens doses for operators.